Pendidikan Pembelajaran Agama Islam Sebagai Karakter dalam Membentuk Kepribadian Siswa yang Islami - Andi Fadhilah Natsir; Ariesthina Laelah (Journal on Education, 2023)
This research explores the use of Islamic religious teaching in an effort to shape the Islamic personality of Muslim students. The research used is qualitative research. The research methodology uses multidisciplinary methods from various fields, including management, pedagogy, sociology, and psychology. Islamic Education instructors are the main data source for this study. The study also used theories on learning methodology, school profiles, Islamic religious education and Muslim personality development as secondary data sources. Observation, interview and documentation were used as data collection methods. The stages of data reduction, data display, and conclusion drawing were used in the data analysis technique. According to the research findings, two learning strategies - direct learning and indirect learning - are used by Islamic religious education to help students develop their Muslim personality. The supporting variables of Islamic Religious Education teachers' strategies in developing students' Muslim personality in terms of Islamic Religious Education learning include: 1) School policy, 2) Teacher collaboration, and 3) Family and community context. The limiting elements are: 1) Students' ignorance about behaviors that show Muslim mentality; 2) Family and community environment. Family and community environment. In order to have a positive impact on students' religious behavior, discipline, and respect for others, the results of the Application of Islamic Education Teacher Strategies in Islamic Education Learning still require improvement and special attention in terms of developing disciplinary behavior.